Rough set clustering approach to replica selection in data grids (RSCDG) - Almuttairi, R M; Wankar, R; Negi, A; Chillarige, R R (2010 10th International Conference on Intelligent Systems Design and Applications, 2010)
In data grids, the fast and proper replica selection decision leads to better resource utilization due to reduction in latencies to access the best replicas and speed up the execution of the data grid jobs. In this paper, we propose a new strategy that improves replica selection in data grids with the help of the reduct concept of the Rough Set Theory (RST). Using Quickreduct algorithm the unsupervised clustering is changed into supervised reducts. Then, Rule algorithm is used for obtaining optimum rules to derive usage patterns from the data grid information system. The experiments are carried out using Rough Set Exploration System (RSES) tool.